Analisis Kesesuaian Praktik Akuntansi Ijarah dengan PSAK 107 : Studi Kasus Lembaga Keuangan Syariah - Mela Desiyanti; Fahman Daffa Haidar; Rusda Diana; M Faqhi Firdaus; Mukhlishotul Jannah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
One type of contract that is very important for the operations of Islamic financial institutions, especially for benefit-based services such as multi-service financing and gold pawnbroking. However, in its application, several problems continue to arise. The most prominent is the incompatibility with Financial Accounting Standards (PSAK) 107 and other Islamic accounting standards in terms of recording and disclosing ijarah transactions. This condition can cause the financial statements of Islamic financial institutions to be less transparent and accountable. Therefore, this study aims to examine how ijarah contracts are used and to what extent the application of ijarah accounting helps Islamic financial institutions become more financially transparent. The research was conducted by reviewing relevant literature, including the provisions of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), PSAK 107, and the fatwa of the Indonesian Ulema Council's National Sharia Board (DSN-MUI). The study shows that the proper use of ijarah accounting, which includes the recognition of ujrah income, the recording of asset gains, and the consistent disclosure of costs, can increase information transparency and stakeholder confidence in financial reports.